Pengaruh Laju Pembebanan Organik terhadap Reduksi Padatan pada Proses Anaerobic Co-Digestion Sampah Sayuran dengan Lumpur SBR - Budhi Primasari; Ansiha Nur (Universitas Andalas, 2018)
Anaerobic digestion is to treat organic waste such as vegetable solid waste (VSW). Anaerobic co-digestion is the mixture of two or more different waste types with the aim to enhance the efficiency of the anaerobic digestion process. In this study, anaerobic digestion of vegetable solid waste (VSW) is compared to the anaerobic co-digestion of VSW and sequencing batch reactor (SBR) sludge. This investigation is focussed on the varying the organic loading rate (OLR) which is the mixing ratio of VSW to SBR sludge; and pH (6, 7 and 8) of the mixture. The mixtures were kept in serum bottles and placed in a shaker for 7 days at 150 rpm. Experiments with OLR 2:1, VSW composition of 1:2:1:1 and pH 6 produced the highest total biogas in anaerobic co-digestion. Thus, for anaerobic co-digestion, the optimum composition of VSW, OLR and pH are 1:2:1:1, 2:1 and 6 respectively. The range of % reduction in total solids (TS), total suspended solids (TSS) and total dissolve solids (TDS) in anaerobic co-digestion is 4-46, 0-43 and 0-64 respectively. In a comparison with single digestion, only 1 in 5 samples of co-digestion exceed that amount of biogas produced by single digestion and this shows that single anaerobic digestion resulted in higher biogas yield. The range of % reduction in TS, TSS and TDS in anaerobic digestion is 13-54, 15-66 and 9-58 respectively. Comparatively, single digestion performs better in solids removal than anaerobic co-digestion and thus, co-digestion method may not be suitable for all types of organic waste.